2014
DOI: 10.1016/j.proeng.2014.12.113
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Vibration of the Vehicle Model with Higher Degree of Freedom

Abstract: New method of solution of the motion equation of the mechanical system with higher degree of freedom is applied on the investigation of the vertical vibration of the vehicle. Mechanical model is composed from three spatially elastically supported and bounded bodies. Model represents the chassis of railroad vehicle with elastic and dissipative elements. Proposed method enables to determine the vertical displacement of the arbitrary point of the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…x Rotational dynamics of gun breech about Y axis in the XZ plane. This is expressed in equation (16).…”
Section: Equations Of Motion For the Elevation Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…x Rotational dynamics of gun breech about Y axis in the XZ plane. This is expressed in equation (16).…”
Section: Equations Of Motion For the Elevation Dynamicsmentioning
confidence: 99%
“…15 A mechanical model is developed, comprising three spatially and elastically supported bounded bodies, in which a new solution method for the equations of motion with higher degrees of freedom, is proposed. 16 A rail vehicle with elastic and dissipative members has been considered, in which, the vertical vibrations at any arbitrary position in the vehicle could be determined based on the above model. 16 A field test is conducted on a military tracked vehicle, in order to analyse the accelerations at selected locations on the vehicle for different types of terrains and different speed conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, there are three main classes of dynamic interactions between rails and sleepers: vertical, lateral and torsional. Vertical rail-sleepers interactions are responsible for damage and service life of the system [3] demonstrated that. Lateral and torsional interactions usually influence the safety against derailment of train and wear of wheels and rails.…”
Section: Introductionmentioning
confidence: 99%
“…The main assumption is the decoupling of lateral and vertical motions. [11][12][13][14][15][16] The lateral dynamics of the RV system is mainly included in curved tracks. Based on the RV structural symmetry, Nejlaoui et al 11 have developed a quarter RV model, which has 8 DOF.…”
Section: Introductionmentioning
confidence: 99%
“…Hou et al 14 considered a vertical RV model with 10 DOF to quantify the vibration of the RV system excited by a wheel flat defect. To determine the vertical vibration of RV system, Soukup et al 15 developed a vertical RV dynamic model with 9 DOF. Sun and Dhanasekar 16 developed a dynamic model, with 10 DOF, to examine the vertical interaction of the rail track and the wagon system.…”
Section: Introductionmentioning
confidence: 99%